Development of a goal setting and goal management system: Intervention Mapping - Kang, Eunyoung; Foster, Erin R. (Frontiers in Rehabilitation Sciences, 2024)
Background: Although goal setting and goal management (GSGM) is a key component of chronic disease management and rehabilitation practice, there is currently no widely used evidence-based intervention system available. This paper describes the theoretical underpinnings and development of a new intervention called MyGoals. MyGoals is designed to guide occupational therapy (OT) practitioners to implement theory-based, client-engaged GSGM for adults with chronic conditions in community-based OT rehabilitation settings. Methods: We first developed a planning team with two adults with chronic conditions, two clinicians, and two researchers. As a collaborative team, we co-developed MyGoals by following Intervention Mapping (IM) steps 1-4 and incorporating community-based participatory research principles to ensure equitable, ecologically valid, and effective intervention development. In the first step, the planning team conducted a discussion-based needs assessment and a systematic review of current GSGM practice to develop a logic model of the problem. In the second step, the planning team identified performance objectives, intervention target personal determinants, and change objectives, and created a logic model of change and matrics of change objectives. In the third step, the planning team designed MyGoals. Lastly, in the fourth step, the planning team produced, pilot-tested, and refined MyGoals. Results: The ultimate goal of the MyGoals intervention is to enable clients to achieve personally meaningful rehabilitation goals. The planning team identified four target determinants (e.g., self-efficacy), six intervention activities (e.g., Education, Reflection, Find My Goals, Make My Goals, Make My Plans, My Progress), eight performance objectives (e.g., List potential goals), and 26 change objectives (e.g., Understand the importance of GSGM). Two pilot tests indicated that MyGoals is feasible for clients and identified areas for improvement. Based on the feedback, minor refinements were made to the MyGoals intervention materials. Conclusions: We completed rigorous and collaborative IM to develop MyGoals. Establishing the theoretical and developmental foundation for MyGoals sets the groundwork for high-quality, evidence-based GSGM. Future studies on effectiveness and implementation are necessary to refine, translate, and scale MyGoals in rehabilitation practice.